Relations among protective behavioral strategies, biological sex, and ADHD symptoms on alcohol use and related problems: Who benefits most, and from what type of strategy?. (August 2021) - Looby, Alison; Prince, Mark A.; Vasko, John M.; Zimmerman, Lauren; Lefler, Elizabeth K.; Flory, Kate; Canu, Will; Hartung, Cynthia M.
Highlights: SLD and MOD PBS negatively relate to alcohol use for students high in inattention. SLD and MOD PBS negatively relate to problems for students high in ADHD symptoms. Sex was a moderator in SLD and MOD models, with strongest effects for males. SHR PBS negatively relate to consequences regardless of ADHD symptoms or sex. Abstract: Attention-deficit/hyperactivity disorder (ADHD) symptoms among college students are associated with high rates of alcohol use and alcohol-related consequences. Use of protective behavioral strategies (PBS) is generally related to lower levels of alcohol use and problems; however, it is unclear how effectively students with ADHD symptoms can implement PBS, and whether certain types of PBS use may yield better outcomes. This study examined relations between PBS type and ADHD symptoms on both alcohol use and consequences, and whether these relations varied by biological sex. Participants were 875 college student drinkers from three universities who completed measures of ADHD symptoms, PBS, past-month alcohol use, and alcohol-related consequences. There were significant moderation effects of ADHD symptoms, such that the relation between PBS use and alcohol use was more pronounced for students high in inattention, and the relation between PBS use and alcohol-related consequences was more pronounced for students high in either inattention or hyperactivity/impulsivity symptoms. These relations were found for both manner of drinking and stopping/limiting drinking PBS, and they tended to be strongest for male students. There were no significant interaction effects that included serious harm reduction PBS; for all students, increased use of this type of PBS was associated with fewer problems. These results suggest that PBS are likely effective for students with ADHD symptoms. Interventions that provide explicit instruction in employing PBS, particularly related to manner of drinking and stopping/limiting drinking strategies, are recommended for students with ADHD symptoms.